Metformin may alter the course of Leber’s hereditary optic neuropathy: a case report - Shenoda Abd Elmaseh; Danielle A. Gauthier; Danielle A. Gauthier; Maryam Golmohammadi; Maryam Golmohammadi; Nutsa Pargalava; Valerio Carelli; Valerio Carelli; Alfredo A. Sadun; Alfredo A. Sadun (Frontiers in Medicine)
Leber’s hereditary optic neuropathy (LHON) is a rare inherited mitochondrial disease caused by variants in mitochondrial DNA (mtDNA) transmitted exclusively through the maternal line. The disease predominantly affects young males and is characterized by progressive bilateral vision loss. Idebenone, a well-studied drug, modestly enhances the mitochondrial function and visual acuity in many patients with LHON. In this study, we report the case of a 48-year-old woman diagnosed with LHON (m.11778G>A/MT-ND4) and type 2 diabetes mellitus who experienced visual field improvement following metformin treatment after 26 months of progressive vision loss unresponsive to idebenone, nicotinamide adenine dinucleotide (NAD+), and hormone replacement therapy (HRT). Our findings offer an intriguing perspective on LHON management but require more investigations, particularly on the molecular effects of metformin on the mitochondrial function in LHON patients.